Kualitas Laporan Keuangan Zakat: Literature Review Study - Wemi Aryuna; Aidil Novia; Maisya Pratiwi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Purpose: This study aims to conduct a literature review study on the quality of zakat financial reports (KLK) at BAZNAS and LAZ in Indonesia. Method: This study used 30 journal articles published in the Google Scholar database indexed by SINTA 1-4 and Google Scholar, articles were selected through inclusion and exclusion criteria using the PRISMA flow diagram. Results: This study found that most of the research on KLK zakat discussed the factors that influence KLK zakat, the most widely used method is quantitative with a descriptive approach, the theory that is often used is stewardship theory, with the most widely studied variable being internal control. Implications: This study shows that there are 12 factors that influence KLK that can be considered by BAZNAS/LAZ to improve the KLK produced. Currently, it is found that research studies on KLK zakat are still very limited. Novelty: This study provides significant contributions through a literature study approach, which integrates findings from previous studies to provide more comprehensive and in-depth information. In addition, this study also fills the research gap by applying literature studies in the context of the quality of zakat financial reports, which has never been done before.